2011
DOI: 10.4049/jimmunol.1100943
|View full text |Cite
|
Sign up to set email alerts
|

Granule-Derived Granzyme B Mediates the Vulnerability of Human Neurons to T Cell-Induced Neurotoxicity

Abstract: Multiple sclerosis (MS) is considered an autoimmune disease of the CNS and is characterized by inflammatory cells infiltrating the CNS and inducing demyelination, axonal loss, and neuronal death. Recent evidence strongly suggests that axonal and neuronal degeneration underlie the progression of permanent disability in MS. In this study, we report that human neurons are selectively susceptible to the serine-protease granzyme B (GrB) isolated from cytotoxic T cell granules. In vitro, purified human GrB induced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 69 publications
(95 reference statements)
2
46
0
1
Order By: Relevance
“…Axoplasmic GzB activity may also serve as a final axon execution mechanism for the indirect injury of neurons and axons. Bystander axon injury is reported in model systems of myelin antigen-directed and astrocyte-targeted CTLs 45-48 and experiments using gang culture neurons demonstrate that purified GzB and exogenously applied lytic granules containing GzB are capable of destabilizing the axon cytoskeleton 49,50 . Therefore, regardless of the mechanism by which lytic granules encounter the axon, either through direct targeting by axon-specific CTLs, as presented in this work, or by collateral diffusion from glia-targeted immune synapses, the introduction of active GzB into the axoplasm may prove singularly sufficient to injure axons.…”
Section: Discussionmentioning
confidence: 99%
“…Axoplasmic GzB activity may also serve as a final axon execution mechanism for the indirect injury of neurons and axons. Bystander axon injury is reported in model systems of myelin antigen-directed and astrocyte-targeted CTLs 45-48 and experiments using gang culture neurons demonstrate that purified GzB and exogenously applied lytic granules containing GzB are capable of destabilizing the axon cytoskeleton 49,50 . Therefore, regardless of the mechanism by which lytic granules encounter the axon, either through direct targeting by axon-specific CTLs, as presented in this work, or by collateral diffusion from glia-targeted immune synapses, the introduction of active GzB into the axoplasm may prove singularly sufficient to injure axons.…”
Section: Discussionmentioning
confidence: 99%
“…Once infiltrated in the brain, inflammatory factors released from T cells may injure neurons or impair the normal functions of local neural stem cells, resulting in loss of functional neurons and delay of recovery [4,5]. We have previously reported that granzyme B (GrB) released from activated T cells inhibits neurogenesis in adult animals and in cultured human fetal neural stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cultures of human fetal neurons (HFN) were generated from 15–19-week fetal brains (obtained with consent from the University of Alberta Ethics Committee) as described [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Cultures of human fetal neurons (HFN) were obtained with consent from the University of Alberta Ethics Committee as described [26]. MS cerebral sub-ventricular deep white matter samples were obtained from the NeuroResource Tissue Bank, UCL Institute of Neurology, London, and UK MS Biobank, with next-of-kin informed consent for tissue donation and ethical approval from Central London REC1 (I.D.08/H0718/62) and approval for the study from the Local Research Ethics Committee (I.D.04/Q2102/111).…”
Section: Acknowledgementsmentioning
confidence: 99%